STRUKTUALISME DALAM PENGINTERPRETASIAN NILAI-NILAI HUMANITAS TEKS - Bani Badadurrakhman (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2019)
Struktualisme as a philosophical school language used for the interpretationof the text, so that the text is not only understood as a religious doctrinethat brings religious doctrines to be followed by a full worship and completeobedience. But to be studied, analyzed and diamlakan ajaranya not as adoctrine adhered to, but rather the awareness and consciousness of thisis expected to arouse humanity to spirituality and religion. In addition,the orientation of this approach focused on two things: the text itself andthe reader in the production of meaning through a process of reasoning,so that the text has its own structure (meaning) and the reader has itsown structure (based on the process of reading and reasoning). Then bothinseparable and intertwined text will not be meaningful if it is not throughthe process of interpretation while the reader does not only rely on reasonbut remain grounded in the text. For as good as any reasonable man wouldnot be able to achieve what the will of God. Moreover, the point of the pointsof this polemic is the interpretation of Al-Maidah 51 so that the writing isalso helped to focus on the paradigm of the public in understanding thetext, especially on Al-Maidah 51 which, when linked to cases of blasphemyhaveledtoconÁicthorizontalanataraMuslimsandnon-Muslimssothathelped worsen the existing identity politics. Therefore, this paper offers analternative approach to text contributed by struktualisme.